GEOMETRY INSTRUCTION BASED ON THE 5E LEARNING CYCLE WITH DGS INTEGRATION TO ENHANCE STUDENTS’ SPATIAL SKILLS - Prasetya, Natan; Sembiring, Maximus Gorky; Sudirman, Sudirman (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Students’ mathematical visual-spatial ability is a key component in understanding geometry, and students need to master this skill. However, the level of students' mathematical visual-spatial ability is less than optimal, so quality learning is necessary. The purpose of this study was to test the quality of the Geogebra-assisted 6E-Instructional Model (6E-IM) on students' spatial visual ability; test the effect of Geogebra-assisted 6E-IM on spatial visual ability; and describe students' spatial visual ability after receiving the Geogebra-assisted 6E-IM model. This study used an embedded design. The independent variable in this study was the Geogebra-assisted 6E-IM, and the dependent variable was spatial visual ability. The variables of the 6E-IM learning model assisted by Geogebra were measured using interviews, while visual spatial abilities were measured using questionnaires. The results showed that the geometry learning instrument with the 6E-IM learning model assisted by Geogebra was in the very good category with a score of 92%. The 6E-IM learning model assisted by Geogebra had a positive effect on students' visual spatial abilities.. Description of students' spatial visual ability involving 2 students in each category, in the high category, met all indicators of spatial visual ability; students with moderate spatial visual ability met two indicators of spatial visual ability; and students with low spatial visual ability met one indicator of spatial visual ability. The results of this study are expected to be Geogebra integrated 6E-IM Design can be used by teachers to improve students' visual spatial abilities.